2020
DOI: 10.3389/fonc.2020.00965
|View full text |Cite
|
Sign up to set email alerts
|

Heme-Dependent ER Stress Apoptosis: A Mechanism for the Selective Toxicity of the Dihydroartemisinin, NSC735847, in Colorectal Cancer Cells

Abstract: Colorectal cancer (CRC) is a leading cause of cancer death in the United States. Artemisinin derivatives, including the dihydroartemisinin (DHA) monomers, are widely used as clinical agents for the treatment of malaria. Numerous studies demonstrate that these molecules also display antineoplastic activity with minimal toxicity. Of interest, dimeric DHA molecules are more active than their monomeric counterparts. Our previous data showed that the DHA dimer, NSC735847, was a potent inducer of death in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…In different model systems, PERK was the predominant regulator of DAMP induction and cell death [ 9 , 11 ]. Therefore, to gain insight into mechanisms underlying 15dPMJ 2 -induced DAMP exposure, the ER stress pathway was probed utilizing the small-molecule PERK inhibitor, GSK2606414 [ 10 ]. 15dPMJ 2 -mediated cell surface expression of CRT was abrogated by GSK2606414 in B16F10 cells ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In different model systems, PERK was the predominant regulator of DAMP induction and cell death [ 9 , 11 ]. Therefore, to gain insight into mechanisms underlying 15dPMJ 2 -induced DAMP exposure, the ER stress pathway was probed utilizing the small-molecule PERK inhibitor, GSK2606414 [ 10 ]. 15dPMJ 2 -mediated cell surface expression of CRT was abrogated by GSK2606414 in B16F10 cells ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…To reestablish ER homeostasis, three sensors: PERK, IRE-1, and ATF6 are activated to promote cell survival. However, if the levels of ER stress are insurmountable, transcriptional activation of CHOP10 leads to the initiation of programmed cell death [ 10 ]. In numerous studies, DAMP inducing agents required the activity of PERK to initiate DAMP emission and cell death [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have indicated that ARTs increase the expression of cleaved caspase-3 and PARP in a variety of cancer cells by producing excessive amounts of ROS, thus inducing apoptosis in cancer cells ( 98 100 ). Further, excessive amounts of ROS may trigger an ER stress response in cancer cells ( 99 ), but the specific mechanism is not clear. Interestingly, increasing the concentration of ferrous ions and oxygen in the tumor environment to further increase the concentration of ROS has been shown to enhance the anticancer activity of ARTs ( 101 , 102 ), which provides a possible strategy for the development of new anticancer drugs based on ARTs.…”
Section: Progress On the Use Of Artemisinin And Its Derivatives For Treating Cancermentioning
confidence: 99%
“… 87 Artemisinin (malaria treatment) derivatives may be an alternative to oxaliplatin, as they are cytotoxic against colon cancer cells lines at low concentrations when used in combination with leucovorin and 5-fluorouracil (FOLNSC combination). 88 …”
Section: Introductionmentioning
confidence: 99%